5-HT1B receptor-AC-PKA signal pathway in the lateral habenula is involved in the regulation of depressive-like behaviors in 6-hydroxydopamine-induced Parkinson's rats. (1st February 2023) - Tang, Guo Yi; Wang, Run Jia; Guo, Yuan; Liu, Jian
ABSTRACT: Objective: The aim of the present study was to investigate whether serotonin1B (5-HT1B ) receptor-adenylate cyclase (AC)-protein kinase A (PKA) signal pathway in the lateral habenula (LHb) is involved in Parkinson's disease-related depression in sham-lesioned and substantia nigra pars compacta (SNc)-lesioned rats. Methods: The sucrose preference and forced swim tests were used to measure depressive-like behaviors. In vivo electrophysiology and microdialysis were performed to observe the firing activity of LHb neurons and GABA and glutamate release in the LHb, respectively. Western blotting was used to analyze protein expression of 5-HT1B receptors, AC and phosphorylated PKA at threonine 197 site (p-PKA-Thr197) in the LHb. Results: Unilateral 6-hydroxydopamine lesions of the SNc in rats induced depressive-like behaviors. Intra-LHb injection of 5-HT1B receptor agonist CP93129 produced antidepressant-like effects and the antagonist SB216641 induced depressive-like behaviors in sham-lesioned and SNc-lesioned rats. Further, pretreatment with AC inhibitor SQ22536 and PKA inhibitor KT5720 blocked the behavioral effects of CP93129 in the two groups of rats, respectively. CP93129 decreased the firing rate of LHb neurons and release of GABA and glutamate, but increased the GABA/glutamate ratio, while SB216641 induced the opposite effects. Compared with sham-lesioned rats, effects of CP93129 and SB216641 on the depressive-like behaviors, electrophysiology, and microdialysis were decreased in SNc-lesioned rats, which were associated with decreased expression of 5-HT1B receptors, AC and p-PKA-Thr197 in the LHb. Conclusion: 5-HT1B receptor-AC-PKA signal pathway in the LHb is involved in the regulation of depressive-like behaviors, and depletion of DA reduces activity of 5-HT1B receptor-AC-PKA signal pathway.